Online Faculty Development and Assessment System (OFDAS) - Luis M. Villar; Olga M. Alegre (International Review of Research in Open and Distributed Learning, 2006)
The rapid growth of online learning has led to the development of faculty inservice evaluation models focused on quality improvement of degree programs. Based on current 'best practices' of student online assessment, the Online Faculty Development and Assessment System (OFDAS), created at the Canary Islands, was designed to serve the dual purpose of faculty development and classroom learning environment assessment. Results, as illustrated in this paper, show that the OFDAS encouraged faculty to reflect on the professionalism of their teaching skills. Implications are discussed in terms of emphasizing the process of online teaching, knowledge acquisition, and incorporating varying perspectives, all which yielded a comprehensive view of faculty teaching attitudes and their relationship to student's perceptions of their classroom environment.